Primary Squamous Cell Carcinoma in the Testis: A Case Report - Kim, Na Rae (The Korean Academy of Medical Sciences, 2010)
A 51-yr-old man presented with an enlarged right testis for two months. The radically resected testis showed a relatively well-circumscribed ovoid mass, nearly replacing the normal architecture with central cystic changes. Microscopically, the mass was composed of ovoid shaped tumor cells of a moderately differentiated squamous cell carcinoma (SCC). The central portion of the mass was filled with well-formed laminated keratinous materials and the remnant cavity lined by dysplastic squamous epithelium, indicated SCC may be derived from an epidermal cyst. SCC is among the most common types of neoplasm afflicting human beings, but it is rare in the testis. To our knowledge, this is the second report of the testicular squamous cell carcinoma occurring in a patient without other primary tumors, and the firstly reported case in Korea.